Investigation of teeth engagement conditions of cylindrical involute gear on contact strength, wear and durability. Part 1. Constant interaction conditions in non-correlated engagement - Чернець, М.В.; Чернець, Ю.М. (Problems of Tribology, 2015)
According to calculation method of tooth gears wear and durability there was conducted an investigation of influ-ence of double – single – double - tooth engagement on maximal contact pressures, teeth wear and gear durability at constant contact conditions in non-correlated helical gearing. It is suggested the method of defining the angles of transition from dou-ble to single-tooth engagement and vice versa. It has been established that maximal contact pressures at the entry into double- and single-tooth engagement are similar. Maximal wear is achieved at the entry into single-tooth engagement (spur gear) or at the entry into double-tooth engagement (helical gearing). The obtained results are presented graphically what allows trac-ing the regularities of influence of engagement conditions.